A guide to walking meditation - Hanh, Thich Nhat.; Huong, Anh.; Bobrow, Joseph (Taiwan : The Corporate Body of the Buddha Educational Foundation)
Thich Nhat Hanh teaches methods of meditation while walking.
Keywords: Meditation -- Buddhism; Meditation -- Zen Buddhism; Buddhist meditations